Chronology of the Cold War, 1917-1992 - Brune, Lester H. (Routledge, 2006)
More than just a timeline, the Chronology of the Cold War is in-depth chronological narrative organized into sections. Each section carries a clear date and summary heading. The five major sections are I. Cold Peace, 1917-1940 II. The Strange Alliance, 1941-1945 III. Containment and Detente, 1946-1975 IV. Confrontation et Conciliation, 1976-1991 V. Epilogue Based on sections of the Chronological History of U.S. Foreign Relations (Routledge 2003), the book includes significant additional material on Russia, China, arms control, and the Cold War in the Third World. This easy-to-use reference also includes an introductory section reviewing the history leading up to the Cold War from 1917 to 1945, a general bibliography of resources on the Cold War and is illustrated with photographs from presidential libraries and 18 maps."--Publisher description